Sex, Technology and Public Health - Davis, M. author. aut Link
VII, 198 p.
Keywords: Exploring the implications of the internet and bio-technologies for intimate and sexual life, this book discusses the concept of citizenship in relation to the extension of public health through the internet, and reveals concerns that sexually transmitted infections and HIV are associated with such technologies.